Pengembangan model strategi serangan “between the line” dalam permainan futsal - Muhammad Yusuf Habibi; Asep Ardiyanto; Maftukin Hudah (YLPK Mahardhika, 2021)
This research method is development, (Research and Development). This research was conducted in 6 stages, namely: 1) and 2) Small-scale field trials practicing unopposed attack strategies, 3) and 4) Large-scale trials with a match system with one's own team, 5) and 6) Large-scale trials with match system with different teams. Based on the results of validation carried out by material experts and media experts, the final percentage is 93% (3-1 Easy), 95% (2-2 Normal), 93% (3-1 Difficult), 93% (3-1 Very Difficult) ). For a small scale player response questionnaire obtained a percentage of 90.6% (3-1 Easy), 83.7% (2-2 Normal), 90.6% (3-1 Difficult), 88.1% (3-1 Very difficult) and large scale get the percentage of 92.2% (3-1 Easy), 88.75% (2-2 Normal), 94.7% (3-1 Difficult), 93.4% (3-1 Very difficult) ). For the results of observations, small-scale researchers get a percentage of 100% (3-1 Easy), 100% (2-2 Normal), 100% (3-1 Difficult), 100% (3-1 Very difficult) and large scale get a percentage of 83 % (3-1 Easy), 42% (2-2 Normal), 83% (3-1 Hard), 83% (3-1 Very Hard). Based on the research results, it was found that the development product was 3-1 Easy Attack Strategy, 2-2 Normal, 3-1 Difficult, 3-1 Very difficult in the form of Storyboard Script and analysis video